Exploring the Motivational Factors for International Students to Study in Chinese Higher Education Institutions - Yasmin, Fakhra; Li, Shengbing; Slaninová, Gabriela (Frontiers in Psychology, 2022)
China has witnessed a remarkable surge in the enrollment of international students in recent years and the state government has made a massive investment to build key universities of international repute. These trends made it imperative to investigate the underlying motivational aspirations of foreign students arriving from diverse regions to get enrolled in public sector Chinese universities. The present study designed an in-depth survey questionnaire and collected data from 618 foreign students enrolled in postgraduate programs at seven key state universities in the Hubei province of China. The item-based, dimension-based, and variable-level analysis approach is used to systematically uncover the facets of the internationalization of Chinese higher education in the current setting. In so doing, we employ descriptive statistics, principal component analysis, ANOVA, correlation and regression estimations, and path models to ensure the robustness of empirical outcomes. In light of the push and pull factor model regarding motivational factors for foreign students to study in China, the findings of this study assert that academic pursuits mainly dictate the international student’s decision to attain higher education in China. While obtaining a foreign degree, international image prestige, and better employment prospects after the completion of the degree were the key intentions that mainly shape the students’ decision to get enrolled in Chinese universities. Furthermore, the discriminant analysis posits that international students significantly differ in their motivational dimensions to obtain a higher degree from China. As foreign students from Asia and Africa mainly have academic goals while Europeans and Americans predominantly have pleasure and enjoyment motives to study in China. The outcomes of this research can assist Chinese administrators to understand the key motivational factors for foreign students to study in China and devise a policy accordingly to attract high quality foreign talent.